English Language Learning Motivation on Eight Grade Students’ of SMP Satria Dharma Perbaungan - Rizka Hasni, Yugi Diraga Prawiyata (Pusdikra-Publishing.com, 2023)
The Purpose of this study is to know the students’ motivation in learning English at the Eigth Grade of Junior High School Satria Dharma Perbaungan. The researcher took 44 students as the sample. This reseach used qualitative method. In collecting the data, the researcher distributed questionnaire to the respondents to measure their motivation in learning English. In analyzing the data, the questionnaire is assessed by rating scale. The result of this research showed that the students’ motivation in learning learning English is 59,31%, and it is categorized into good of motivation. Based on the research finding, it can be concluded that the students have high motivation in learning English.